2010
DOI: 10.1021/la102435f
|View full text |Cite
|
Sign up to set email alerts
|

Simple Coupling Chemistry Linking Carboxyl-Containing Organic Molecules to Silicon Oxide Surfaces under Acidic Conditions

Abstract: The coupling chemistry of carboxymethylated amylose with organo-silanized silicon oxide surfaces at pH 7.4 and 2.0 was investigated using atomic force microscopy (AFM) based single-molecule force spectroscopy. At close to neutral pH, carbodiimide activation of a carboxylic acid affords formation of an amide bond with an amino surface linker. At pH 2.0, no activation with carbodiimide was required to anchor carboxymethylated amylose between an AFM tip and a glass substrate. At the same time, the mean bond ruptu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 55 publications
3
29
0
Order By: Relevance
“…44 The conducted experiments revealed biexponential rupture kinetics, which have been rationalized with the silyl ester hydrolysis depending on the moieties at the silicon atom under acidic conditions.…”
Section: Introductionmentioning
confidence: 88%
“…44 The conducted experiments revealed biexponential rupture kinetics, which have been rationalized with the silyl ester hydrolysis depending on the moieties at the silicon atom under acidic conditions.…”
Section: Introductionmentioning
confidence: 88%
“…This suggests complete conversion of carboxyl groups into phenol groups. Previous studies have shown that proteins can be immobilised onto silicon oxide or PEG surfaces using this chemistry [30,31]. Glycosaminoglycans have also been conjugated to PEG hydrogels using the same chemistry [26].…”
Section: Synthesis Of Pva-tyrmentioning
confidence: 99%
“…In the vast majority of successful attachments, only a single rupture event was observed, which is associated with rupture of the silane surface anchor. [11][12][13][14]19] Table 1). The inset shows that the slope of the force-extension curve is the same before and after the rupture.…”
mentioning
confidence: 99%